Mussolini's Army against Greece - Carrier, Richard, 1965- author.
1 online resource (207 pages).
Keywords: "This book analyses why the Italian army failed to defeat its Greek opponent between October 1940 and April 1941. It examines the multiple forms of ineffectiveness that plagued the political leadership as well as the military organization. Mussolini's aggression of Greece ranks among the most neglected campaigns of the Second World War. The book proposes that compared to the North African and Russian campaigns where the Regio Esercito achieved a decent level of military effectiveness, this was a military fiasco. It will appeal to anyone interested in the history of the war, and to those involved in the study of military effectiveness and intrigued by why armies fail"--